2012
DOI: 10.1080/10426914.2011.552019
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Influence of Surfacing Process Parameters Over Bead Properties During Stainless Steel Cladding

Abstract: The bead parameters play a vital role in determining and understanding the properties of the weld cladding in fusion welding process. This investigation aims at minimizing weld dilution and predicting the behavior of the bead parameters during weld cladding of AISI 316L (UNS 316 03) metal powder over carbon steel (ASTM A105/ IS: 2062), by plasma transferred arc (PTA) surfacing through response surface method. The data for modeling were collected from experiments conducted using a five level factorial technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In addition, the cross-section shows that there are no defects such as porosity, incomplete fusion, crack, etc [28]. Table.4 gives the total wire melting rate, base metal penetration depth, and the weld bead dilution rate [29] of the above weld beads. From the table it is seen that with the same current, TW-GIA welding more than doubles the wire melting rate.…”
Section: Bead-on-plate Welding Trialmentioning
confidence: 99%
“…In addition, the cross-section shows that there are no defects such as porosity, incomplete fusion, crack, etc [28]. Table.4 gives the total wire melting rate, base metal penetration depth, and the weld bead dilution rate [29] of the above weld beads. From the table it is seen that with the same current, TW-GIA welding more than doubles the wire melting rate.…”
Section: Bead-on-plate Welding Trialmentioning
confidence: 99%
“…The dilution in PTAW process usually varies between 5% and 20% for high deposition rate and it can be reduced up to zero percent at low deposition rate [13,14]. It has also been observed that the dilution is more sensitive to arc current and scanning speed than to powder feed rate [15].…”
Section: Introductionmentioning
confidence: 97%
“…Lakshminarayanan et al [10] and Barroi et al [11] have described that for high deposition rate, the variation of dilutions are in between 5 to 20% and for low deposition rate, the dilution may be reduce up to zero percent. Robert Jayachandran et al [12] have shown that the effects of scanning speed and current on dilution are more compare to powder feed rate. Xibao et al, [13] Sudha et al [14] and Kumar et al [15] have discussed the effects process parameters on micro-structural analysis of the deposited bead in the PTAW process.…”
Section: Introductionmentioning
confidence: 99%